A low-cost and green-solvent-processable hole-transport material enabled by a traditional bidentate ligand for highly efficient inverted perovskite solar cells. Issue 28 (29th June 2021) - Huang, Jiachen; Yang, Jie; Li, Dan; Sun, Huiliang; Su, Mengyao; Ji, Xiaofei; Li, Bolin; Li, Bangbang; Liao, Qiaogan; Han, Dongxue; Yan, He; Niu, Li; et al.
Abstract : A bidentate ligand 1, 10-phenanthroline enables a green-solvent-processable low-cost hole-transport material M1, which efficiently passivates the Pb 2+ ion defects of perovskite toward high-performance inverted perovskite solar cells. Abstract : Low-cost and eco-friendly hole-transport materials (HTMs) are exceedingly desirable for the practical application of perovskite solar cells (PVSCs). Here, a traditional bidentate ligand (1, 10-phenanthroline), widely used as a chelating agent for bioorganic reagents and probes, is incorporated into an HTM to afford M1 . Such a planar bidentate ligand at the central core of the HTM can facilitate π–π stacking and enable chelation to Pb 2+ ion defects and thus achieve efficient passivation at the M1 /perovskite interface, contributing to reduced recombination loss. When employed as an HTM in inverted PVSCs without dopants, bidentate-ligand-based M1 yields a high power conversion efficiency (PCE) of 20.14%, which is significantly higher than that (18.32%) of the M0 analogue that contains phenanthrene. More importantly, green solvent processing (ethyl acetate) of M1 achieves a PCE of 19.21%, which is among the highest values reported in PVSCs with a green-solvent-processable HTM. Besides, the facile one-step synthesis route reduces the cost to 45 gram −1 for M1, which is cheaper than the most reported HTMs for high-efficiency PVSCs without dopants. These findings demonstrate the potential of bidentate ligands in developing cost-effective and eco-friendly HTMs toward highly efficient PVSCs.